Orientasi Fiskal dalam Penegakan Hukum Keimigrasian: Antara PNBP, Tindakan Administratif Keimigrasian, dan Proses Peradilan Pidana - Masdar Bakhtiar; Awaluddin Kadriah; Muhammad Yusuf (Jurnal Ilmiah Kebijakan Hukum, 2026)
This study examines the shift in Indonesia's immigration law enforcement from a sovereignty-based approach toward fiscal orientation, reflected in revenue-oriented enforcement whereby legal instruments increasingly optimize Non-Tax State Revenue (PNBP). This study aims to identify the interrelation between State Budget Allocation (DIPA) design and PNBP targets with enforcement instrument selection, particularly between Immigration Administrative Actions (TAK) and criminal proceedings, and their implications for immigration's selective function and national security. Using a normative-empirical approach, this study analyzes immigration regulations comparatively alongside empirical data from the Directorate General of Immigration's Performance Reports, Ministry Annual Reports, DIPA documents, and in-depth interviews with Technical Implementation Unit officials, applying the economic analysis of law framework. Findings reveal that TAK escalation correlates with PNBP increases while criminal proceedings simultaneously decline, indicating fiscal orientation dominance. Budget analysis uncovers a structural disincentive toward criminal proceedings stemming from DIPA asymmetry between service and enforcement functions, reinforced by PNBP codification as an institutional performance indicator, rationally driving officials toward TAK. This condition weakens immigration's selective function and elevates national security risks. This study recommends revising the immigration DIPA to proportionally increase enforcement budgets and issuing technical guidelines tightening TAK discretionary criteria to rebalance revenue and sovereignty functions.